Incorporation of Corporate Startup: A Definition, Challenge, and Future Research Agenda - Gabriel, Joy; Ekaputra, Irwan Adi; Satrya, Aryana (Universitas Airlangga, 2024)
Objective: A corporate startup is a business development initiative led by a company's employees, using the company's resources and with the support of top managers. It aims to address business problems that arise within the company. This study seeks to define a corporate startup, highlight its challenges, and identify areas for future research. Design/Methods/Approach: The method employed is a literature review based on the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) paradigm, with systematic searches from a database of high-quality scientific journals indexed by Scopus (Q1 and Q2). Selected publications relevant to the theme will be reviewed, and data will be summarized. Findings: This study finds three challenges that occur for corporate startups, namely collaboration development with internal and external corporate startups, finding competent mentors for corporate startups, and resource management competency. Further research can be continued by discussing three things, namely identifying companies that practice corporate entrepreneurship and capturing qualitative and quantitative organizational designs to enable corporate entrepreneurship, more research on developing countries, and the creation of standard standards regarding the evaluation of startup corporate models in various companies across industries and countries. Originality/Value: This research is the first study to describe the definition of corporate startups obtained from various high-quality journals (Scopus Q1 and Q2), which discusses various applications of corporate startups worldwide, the majority in the form of case study studies. With various views on the applications in the industry through Case Studies, this research also explained a review of the challenges and agenda of research in the future Corporate Startup, originating from various practices over the past 20 years on four different continents. Practical/Policy implication: Companies can implement corporate startups by utilizing a model derived from this paper. This involves embracing specific definitions, addressing challenges proactively, and outlining future research directions based on the findings of this study. Academics can also apply future research agendas to subsequent research to develop research related to Corporate Startup.